Avaliação das condições de uso e ocupação do parque Parahyba - João Pessoa/PB. - Faria, Alexandre Brito de (2015)
The process of occupation and expansion in the city of João Pessoa, PB has accelerated considerably in recent years leaving in the wake of this growth a negative balance stop the environment. These problems spill over environmental issues interferes with quality of life. This research aims to diagnose the environmental situation of the Parahyba Municipal Park and suggest mitigation alternatives to the problems identified. This worked used an unmanned aerial vehicle (UAV), satellite images, aerial photographs of 1976, visit the field to collect data and images, was held the georrefereciamento using ArcGIS 10.1 software. This Geographic Information System allowed to form a bank of the main geographic information of the study place. Had with reference subjects such as Landscape Ecology and Restoration due to its integrated vision capacity of the environment. From the results of this research can be observed that although it is incorporated as a conservation area the Park Parahyba save different environmental problems in violation of current law that reduce the environmental quality of the place. The diagnosis allowed also present the role of the park as a producer of environmental services to this part of the city by improving the quality of life.